Maqasid-Based Comparative Jurisprudence: Synthesis of Capitalism, Socialism, and Islamic Economics in Indonesia’s Dual Economic System - Pertaminawati, Hendra; Dewi, Nisrina Mutiara; Prawiro, Teguh (MIZAN: JOURNAL OF ISLAMIC LAW, 2025)
The purpose of this article is to compare legal systems in the concept of ownership (al-Milkiyyah) and examine the integration of Positive Law and Islamic Law in Strengthening Sharia financial institutions in Indonesia. Using a juridical-philosophical approach, this study examines the ontological, epistemological, and axiological aspects of each economic legal system. Ontologically, capitalism is rooted in individual freedom and private property rights; socialism in collectivity and structural equality; while Islam emphasizes the balance between private ownership, social responsibility, and distributive justice. Epistemologically, Western economic law is based on secular rationality and empiricism, while Islamic economic law is derived from revelation and maqāṣid al-syarī‘ah. From an axiological perspective, Islamic economic law prioritizes the values ​​of justice and welfare over material utility. The main findings of this study indicate that the Indonesian dual economic system model represents an epistemological synthesis between Western legal rationality and Islamic legal spirituality. National legal pluralism allows for the coexistence of two complementary economic systems, conventional and sharia, within the framework of equitable economic development. The theoretical implication is the need for a comparative model of economic law based on maqāṣid (maqāṣid-based comparative jurisprudence), while the practical implication is the importance of harmonizing positive legal regulations with sharia principles to achieve an efficient, ethical, and equitable national economic legal system. Keywords: Economic Law, Capitalism, Socialism, Islamic Economics, Dual Economic System, Maqāṣid al-Syarī‘ah.